2018
DOI: 10.1016/j.celrep.2018.02.046
|View full text |Cite
|
Sign up to set email alerts
|

DiSNE Movie Visualization and Assessment of Clonal Kinetics Reveal Multiple Trajectories of Dendritic Cell Development

Abstract: A thorough understanding of cellular development is incumbent on assessing the complexities of fate and kinetics of individual clones within a population. Here, we develop a system for robust periodical assessment of lineage outputs of thousands of transient clones and establishment of bona fide cellular trajectories. We appraise the development of dendritic cells (DCs) in fms-like tyrosine kinase 3 ligand culture from barcode-labeled hematopoietic stem and progenitor cells (HSPCs) by serially measuring barcod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…We modified a classical strategy for clonal labeling by lentiviral delivery of inherited DNA barcodes 15,16 , to allow barcode detection using scSeq 17 . The barcode consists of a random 28-mer in the 3' UTR of an enhanced green fluorescent protein (eGFP) transgene under control of a ubiquitous EF1a promoter (Fig 1b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We modified a classical strategy for clonal labeling by lentiviral delivery of inherited DNA barcodes 15,16 , to allow barcode detection using scSeq 17 . The barcode consists of a random 28-mer in the 3' UTR of an enhanced green fluorescent protein (eGFP) transgene under control of a ubiquitous EF1a promoter (Fig 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Transcripts of eGFP are captured during scSeq, and the barcode is revealed through analysis of sequencing reads. The theoretical number of barcodes for this construct is 4 28 (or ~10 16 ), though bottlenecks in molecular cloning limited the diversity to ~10 6 barcodes, sufficient to label ~10 4 cells in an experiment with <0.5% barcode overlap between clones. We refer to the barcoding construct as LARRY (Lineage And RNA RecoverY).…”
Section: Introductionmentioning
confidence: 99%
“…Recent single cell transcriptional profiling and lineage tracing studies have highlighted substantial lineage bias and lineage restriction within HSPCs that had previously been assumed to be multi-or oligo-potent (Dykstra et al, 2007;Lee et al, 2017;Lin et al, 2018a;Naik et al, 2013;Nestorowa et al, 2016;Notta et al, 2016;Velten et al, 2017;Yamamoto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There could be three possibilities for this: a) there were different molecular routes to the same cell type, and there is precedence for this in DC development 26 ; b) the clusters represent different points of the same developmental trajectory, and the snapshot of our clones captured these different stages; and c) there is heterogeneity within our flow cytometric-sorted populations of DCs and the clusters may represent different clonal routes to these putative subpopulations. Recent evidence suggesting Siglec-H + cells can be further separated by CCR9 expression into cDC progenitors and bona fide pDCs 18,27 , so this might be an example of c) as pDCs were not sorted based on CCR9 in these experiments. That is, Cluster 8 may represent genes that actually correlate with cDC bias, and where cells phenotypically ascribed as pDCs were in fact CCR9 -cDC progenitors.…”
mentioning
confidence: 97%
“…Relevant to SIS-seq is that DCs can be generated in vitro 16 for ease of assessment of multiple clones, and be derived from single HSPCs 11 . Moreover, cellular barcoding and clone-splitting experiments in vivo 17 and in vitro 18 demonstrated that DC lineage bias, and also individual DC subtype bias, is heterogeneous amongst HSPCs, but restricted within a given clone. These properties fit the first two conditions for SIS-seq to be feasible.…”
mentioning
confidence: 99%